Getting organised - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
One of the most notable changes to the rural landscape of late has been the growth of farmers organisations and associations. At the local level, they have replaced or complemented the work of extension bodies, marketing boards and some...